Physically crosslinked PAA/Lys-BPEA hydrogel with rapid self-healing and long-term antibacterial activities. (16th January 2023) - Li, Huan; Li, Yingying; Wang, Yudan; Liu, Lijia; Dong, Hongxing; Zhang, Chunhong; Satoh, Toshifumi
Abstract: Diseases caused by bacterial infections continue to threaten human health around the world. Antimicrobial hydrogels with excellent properties have been developed in biomaterial and other fields in some cases, where overuse or inappropriate use of antibiotics has led to increased bacterial resistance. In this study, primary amines that are rich in lysine end groups were used to synthesize Lys-BPEA crosslinker. An antibacterial self-healing hydrogel (labeled as polyacrylic acid [PAA/]/Lys-BPEA) was prepared by introducing polyamine Lys-BPEA into PAA via ionic bonding and electrostatic interaction. The surface morphology and mechanical properties, especially the antibacterial and self-healing properties, of the created physically crosslinked PAA-lysine polyetheramide hydrogels were investigated. The PAA/Lys-BPEA hydrogel realized a comprehensive performance of long-term antibacterial activity without inducing drug resistance, low hemolysis activity and rapid self-healing ability. Therefore, the performance of the combination makes the PAA/Lys-BPEA hydrogel an ideal candidate for the design of smart self-healing devices and antibacterial surface coatings. Graphical abstract: Image 1 Highlights: The PAA/Lys-BPEA hydrogel with dual-function were successfully prepared. The hydrogels have highly effective and long-term antibacterial ability. The hydrogels exhibits rapid self-healing ability without any external intervention.